PEMANFAATAN CITRA SATELIT ALOS AVNIR-2 SEBAGAI SALAH SATU DATA UNTUK IDENTIFIKASI TANAH TERLANTAR HAK GUNA USAHA UNTUK PERKEBUNAN (Studi Kasus Kabupaten Landak Propinsi Kalimantan Barat) - , Catur Widayanti; Harintaka, ST., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Identification of abandoned land are presently implemented in accordance technical instructions regarding the control and efficient use of abandoned land. Identification by researching juridical and inventory of textual and spatial data. Acquisition of spatial data in the form of land use by field survey methods. Data current land use was used to determine the suitability of use with a regional plan (RTRW) that exist and the purpose of granting rights. Identification with the field survey methods on the location of land cultivation rights title (HGU), which has a relatively wide area coverage with varying field conditions takes time, effort, and considerable expense. Use of satellite imagery for object identification purposes in the earth's surface has been applied. The research was conducted to determine the possible use of ALOS AVNIR-2 image in the identification of abandoned land cultivation rights title for plantations. The study was conducted in HGU of PT. Purna Kahuripan who allegedly abandoned area of 1837.122 ha. Identification of abandoned area have been done by ALOS AVNIR-2 image interpretation using digital classification and transformation vegetation index method. Digital classification is used for mapping land use by detecting of land cover. Land use data obtained from field tests are then used as reference for dividing land cover to obtain land use map. Based on maps of existing land use known to the appropriate use of land or not in accordance with the designation and purpose of their rights. The transformation vegetation index to distinguish vegetation of coconut plantation and non plantation vegetation through vegetation index value. Heterogeneous vegetation on the study area produce vegetation index values vary so difficult to use for identification of abandoned land at the study area. The results digital classification of land use in study area are : open land area 234.585 ha, forest 1097.199 ha, and tundra 505.338 ha. The result of land use classification indicates that the location of the ...